OP0133 Colour doppler ultrasonography of facial and occipital arteries in patients with giant cell arteritis: the frequency of involvement and the role of their assessment in daily practice: a prospective study. (15th June 2017) - Jese, R; Rotar, Ž; Tomšič, M; Hočevar, A
Abstract : Background: Giant cell arteritis (GCA) is the most common systemic large and medium size artery vasculitis in Western countries. Colour Doppler Sonography (CDS) allows us to study the involvement of the cranial arteries other than the temporal arteries in GCA which cannot be safely biopsied such as the facial (FaA), and occipital (OcA) arteries. Objectives: We aimed to estimate the frequency of the FaA, and OcA involvement in GCA; and to explore the clinical characteristics of these subgroups of patients. Methods: From 1 January 2014 to 31 December 2016, we prospectively performed a CDS of the FaA, and OcA in addition to the temporal (TA), and the extracranial supra-aortic arteries in all newly diagnosed patients suspected of having GCA. We used a Philips IU22 with a 5–17.5 MHz multi-frequency linear probe from January 2014 to August 2016 and a Philips Epiq 7 with a 5–18 MHz multi-frequency linear probe from September 2016 to December 2016. All the arteries were evaluated in two planes for the highly specific halo -sign. Results: During the 36-month observation period we performed a CDS of the cranial and extra-cranial arteries in 93 GCA (66.7% female) patients. The patients' median (IQR) age was 73.7 (66.1–79.1) years, and they had a median (IQR) symptom duration of 30 (21–90) days. We observed the halo -sign on the FaA, and OcA in 38 (40.9%), and 29 (31.2%) cases, respectively. The FaA, and OcA were simultaneously affected in 18/93 (19.4%) cases. The FaA, or OcA were affected in 4/22 (18.2%) patients with a negative TA CDS. Patients with an FaA involvement had the highest frequency of severe visual manifestations, with permanent visual loss representing 70% of all visual manifestations. Patients with an OcA involvement least commonly had extracranial large vessel disease. Conclusions: A fifth of patients with a negative CDS of the TAs had signs of vasculitis only on the CDS of the FaA, or OcA. The CDS of the FaA, and OcA identified approximately 5% more patients with GCA than the CDS of the TA alone. Disclosure of Interest: None declared